Behavioral determinants of hand hygiene practices during the COVID-19 pandemic: Insights from the 2020 Community Health Survey - Kwon, Rang-Hee; Jung, Minsoo (Korean Journal of Health Education and Promotion, 2025)
Objectives: This study examined the impact of conventional health behaviors on hand hygiene practices during the COVID-19 pandemic using data from the 2020 Community Health Survey (N=210,089). Methods: Smoking, drinking, and physical activity were assessed as predictors of hand hygiene behavior. For statistical analysis, hierarchical logistic regression analysis was performed while controlling for confounders. Results: Men and older individuals were found to be less likely to practice hand hygiene, while higher education levels increased the likelihood. Smokers and frequent drinkers were less likely to maintain hand hygiene, whereas those engaging in more physical activity and those vaccinated against influenza were more likely to practice it. Conversely, individuals with unsatisfactory medical experiences had lower hand hygiene rates. The study suggests that those with healthier behaviors, such as physical activity and vaccination acceptance, were more likely to engage in proper hand hygiene during the pandemic. However, those with health-risk behaviors, such as smoking and frequent drinking, were less compliant. Conclusion: The findings highlight the need for tailored non-pharmacological interventions targeting high-risk groups who may continue these behaviors during new infectious disease outbreaks. This emphasizes the importance of promoting overall health behaviors to improve preventive measures in future pandemics. KCI Citation Count: 0